53 What are the feeding patterns and outcomes of enterally tube fed paediatric renal transplant recipients?. (22nd November 2019) - Khweir, Sarah; Payne, Anne; Marks, Stephen
Abstract : Introduction: Many children with chronic kidney disease exhibiting symptoms of poor appetite, anaemia and vomiting are reliant on enteral tube feeding (ETF) to help support their nutritional intake. Following a successful renal transplant, these symptoms may resolve and children should be able to wean off ETF. This study explored how long it takes for paediatric renal transplant recipients (pRTR) to discontinue tube feeding after transplantation and the factors which may influence this. Methods: The study included 20 patients aged 1 to 17 years, who had a renal transplant at a single tertiary centre, of whom 14 (70%) were male. Retrospective data analysis of medical and dietetic records from 1 January 2014 to 31 December 2017, was performed using IBM SPSS for statistical analysis, with a p value of < 0.05 considered significant. Results: 70% (14 of 20) pRTR discontinued ETF at 0 - 70 (median six) weeks post-transplant. Patients had been ETF from 0 - 10.8 (median 0.45) years, for 1.1 - 10.9 (median 3.9) years prior to receiving a transplant. There was no oral aversion by 18 months post-transplant, although four children (20%) were referred to the behaviour feeding clinic at 2 - 44 (median 24) months post-renal transplantation. BMI z-score of 0.43 at 12 months pre-transplant was found to be significantly associated with shorter duration of ETF post-transplant (r=0.8, p=0.001). Conclusions: While half of pRTR weaned off their ETF within six weeks post-transplantation, regardless of age or duration of tube feeding prior to transplant, this study has demonstrated that a good nutritional status pre-transplant may be helpful in reducing length of ETF post-transplant. A small number of children will experience behavioural feeding issues post-transplant. Future research involving multi-centre studies will provide more robust results.